Urban dynamics and growth : advances in urban economics - Capello, Roberta, 1962-; Nijkamp, Peter (Amsterdam ; Oxford : Elsevier, 2004)
Offers a collection of advanced theories and methods in the field of urban policies, and highlights modern urban policies that stem from them. This title focuses on the urban policies, as well as practical problems envisaged in our modern cities, that take advantage from the theoretical development.
Includes bibliographical references and index.
oif 09/03/14
Loan
Keywords: Urban economics; Economics; Cities and towns -- Growth -- Mathematical models